The patristic concept of the deification of man examined in the light of contemporary notions of the transcendence of man - Cullen, J; Cullen, John Austin (1986)
﻿ This thesis examines the proposition that there is a correspondence between the concept of human self-transcendence and the concept of the deification of man in that both are concerned with the bringing of human nature to its fulfilment by a process of 'redemption'. The first issue addressed is what it means to speak of man participating in divinity, and this notion is then traced through the religion and philosophy of the ancient classical world and the later Graeco-Roman world as the background against which early Christian doctrine emerged. Some modern interpretations of the notion of transcendence as it relates to the human existent are then reviewed, with particular attention being given to the suggestion that it is legitimate to speak of man rather than God as the 'locus' of transcendence by virtue of the inherent openness of human nature to the transcendence of being that meets it in its ex-sisting in being. The second, third and fourth chapters examine the development of the concept of deification as a way of speaking of humanity being brought to a resemblance to God, partaking of the divine nature, and thereby being enabled to realize the image of God in which man was originally created. The fifth chapter investigates the contributions of a selection of contemporary thinkers on the notion of man's quest for fulfilment by the process of self-transcendence, that process of overcoming the aspects of being human which compromise and threaten actual human existence. The final chapter shows how the insights of contemporary thought on the concept of self-transcendence can illuminate for us the patristic concept of deification as a way of speaking about the nature and destiny of human existence and the thesis concludes with a suggestion of three areas of contemporary investigation to which this study might be related.